Effects of Environmental Innovations, Renewable Energy Consumption and Economic Growth on CO2 Emission: Panel Data Analysis for Select G-20 Countries - Demez, Selim (Muş Alparslan Üniversitesi, 2021)
Environmental problems are becoming more visible and this detrimental situation, negatively affecting the national economies. Therefore, the economic effects and costs of environmental problems have become an important research topic in the field of economics. In the literature, carbon dioxide (CO2) emission is generally used as an environmental pollution indicator. It is thought that renewable energy investments and innovative approaches to the environment can overcome environmental problems in the long run. In this study, the effect of environmental innovations (ETI), renewable energy (REC) and growth (GDP) on CO2 emission examined for 8 countries, listed according to the IMF's classification in the G-20 country group between 1993 and 2018. Durbin-H cointegration and FMOLS tests are used in the analysis, considering the cross-sectional dependency and heterogeneity. According to the analysis results, there is a long-term relationship between the variables. The effects of the variables considered on CO2 emission differ by country, the change in REC and GDP for the panel generally reduces CO2 emission, while the increase in ETI increases CO2 emission.

Çevresel problemler her geçen gün katlanarak artmaktadır ve bu durum doğrudan ve dolaylı olarak ülke ekonomilerini de olumsuz yönde etkilemektedir. Bu nedenle çevresel problemlerin ekonomik etkileri ve maliyeti iktisat alanında önemli bir araştırma konusu haline gelmiştir. Çevresel kirlilik göstergesi olarak literatürde genellikle karbondioksit (CO2) emisyonu kullanılmaktadır. Yenilenebilir enerji yatırımları ve çevreye yönelik inovatif yaklaşımların uzun dönemde çevresel problemlerin üstesinden gelebileceği düşünülmektedir. Bu çalışmada çevresel inovasyonlar (ETI), yenilenebilir enerjinin (REC) ve büyümenin (GDP) CO2 emisyonu üzerindeki etkisi 1993-2018 yılları arasında G-20 ülke grubunda IMF’nin sınıflandırmasına göre gelişen statüsündeki 8 ülke için incelenmiştir. Analizde yatay kesit bağımlılığı ve heterojenliği dikkate alan Durbin-H eşbütünleşme ve FMOLS testleri kullanılmıştır. Analiz sonuçlarına göre değişkenler arasında uzun dönemli bir ilişki vardır. Ele alınan değişkenlerin CO2 emisyonu üzerindeki etkileri ülkeden ülkeye farklılık göstermektedir fakat panelin geneli için REC ve GDP’deki artışın CO2 emisyonu üzerindeki etkisi negatifken ETI’daki artışın etkisi beklenenin aksine pozitiftir.
Çevresel İnovasyonlar, Yenilenebilir Enerji Tüketimi ve Ekonomik Büyümenin CO2 Emisyonu Üzerine Etkileri: Seçilmiş G-20 Ülkeleri için Panel Veri Analizi
anemon
Keywords: Environmental Innovations; Renewable Energy; Growth; CO2 Emission; Çevresel İnovasyonlar; Yenilenebilir Enerji; Büyüme; CO2 emisyonu